PRODUKTIVITAS PRIMER DAN KONDISI FISIKA KIMIA PERAIRAN SUNGAI RIAM KANAN DESA AWANG BANGKAL KECAMATAN KARANG INTAN KABUPATEN BANJAR - Mukhlisah Mukhlisah; Arthur Mangalik; Rozanie Ramli; Akhmad Naparin (Universitas Lambung Mangkurat, 2011)
Purpose of this research was to know primary productivity rate, concentration of some parameters like as physical, chemical, and biology, and analyze of relationship about physic and chemical parameters to primary productivity rates Riam Kanan river, Awang Bangkal village. Method of the research was survey method, as descriptive research to describe present condition about water quality from the parameters aspect that supported aquaculture activity. Result of this research that primary productivity of Riam Kanan waters, Awang Bangkal village classified poor of nutrition substance (lower productivity). Some of physical parameters (temperature, brightness, and turbidity), chemical parameters (DO, Phosphate, Fe, Nitrate, Mn and oil) were on tolerance level for aquaculture except BOD based on Government Regulation No.82 year 2001 and Shout Kalimantan Governor Regulation No.05 year 2007. Diversity and uniformity indeks of plankton showed that Riam Kanan rivers Awang Bangkal village classified moderate until good polluted category. Relation among water quality parameters with primary productivity rates was not significant in rainy or clear weather day condition.